Assessing Wear Coefficient and Predicting Surface Wear of Polymer Gears: A Practical Approach - Muratovic, Enis; Muminovic, Adil; Pervan, Nedim; Delic, Muamer; Muminovic, Adis; Saric, Isad (Engineering, Technology & Applied Science Research, 2024)
With the ever-increasing number of polymer materials and the current number of commercially available materials, the polymer gear design process, regarding the wear lifetime predictions, is a difficult task given that there are very limited data on wear coefficients that can be deployed to evaluate the wear behavior of polymer gears. This study focuses on the classic steel/polymer engagements that result in a wear-induced failure of polymer gears and proposes a simple methodology based on the employment of optical methods that can be used to assess the necessary wear coefficient. Polymer gear testing, performed on an open-loop test rig, along with VDI 2736 guidelines for polymer gear design, serves as a starting point for the detailed analysis of the wear process putting into service a digital microscope that leads to the evaluation of the wear coefficient. The same wear coefficient, as presented within the scope of this study, can be implemented in a rather simple wear prediction model, based on Archard’s wear formulation. The developed model is established on the iterative numerical procedure that accounts for the changes in tooth flank geometry due to wear and investigates the surface wear impact on the contact pressure distribution to completely describe the behavior of polymer gears in different stages of their lifetime. Although a simple one, the developed wear prediction model is sufficient for most engineering applications, as the model prediction and experimental data agree well with each other, and can be utilized to reduce the need to perform time-consuming testing.